Simulated microgravity disturbs iron metabolism and distribution in humans: Lessons from dry immersion, an innovative ground‐based human model. Issue 11 (12th September 2020) - Nay, Kévin; Koechlin‐Ramonatxo, Christelle; Rochdi, Sarah; Island, Marie‐Laure; Orfila, Luz; Treffel, Loïc; Bareille, Marie‐Pierre; Beck, Arnaud; Gauquelin‐Koch, Guillemette; Ropert, Martine; Loréal, Olivier; Derbré, Frédéric
Abstract: The objective of the present study was to determine the effects of dry immersion, an innovative ground‐based human model of simulated microgravity and extreme physical inactivity, on iron homeostasis and distribution. Twenty young healthy men were recruited and submitted to 5 days of dry immersion (DI). Fasting blood samples and MRI were performed before and after DI exposure to assess iron status, as well as hematological responses. DI increased spleen iron concentrations (SIC), whereas hepatic iron store (HIC) was not affected. Spleen iron sequestration could be due to the concomitant increase in serum hepcidin levels ( P  < .001). Increased serum unconjugated bilirubin, as well as the rise of serum myoglobin levels support that DI may promote hemolysis and myolysis. These phenomena could contribute to the concomitant increase of serum iron and transferrin saturation levels ( P  < .001). As HIC remained unchanged, increased serum hepcidin levels could be due both to higher transferrin saturation level, and to low‐grade pro‐inflammatory as suggested by the significant rise of serum ferritin and haptoglobin levels after DI ( P  = .003 and P  = .003, respectively). These observations highlight the need for better assessment of iron metabolism in bedridden patients, and an optimization of the diet currently proposed to astronauts.